2016
DOI: 10.1038/onc.2016.389
|View full text |Cite
|
Sign up to set email alerts
|

Wwox–Brca1 interaction: role in DNA repair pathway choice

Abstract: In this study, loss of expression of the fragile site encoded Wwox protein, was found to contribute to radiation and cisplatin resistance of cells, responses that could be associated with cancer recurrence and poor outcome. WWOX gene deletions occur in a variety of human cancer types and reduced Wwox protein expression can be detected early during cancer development. We find that Wwox loss is followed by mild chromosome instability in genomes of mouse embryo fibroblast cells from Wwox knockout mice. Human and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 40 publications
8
82
0
1
Order By: Relevance
“…As illustrated in Figure A, normal breast epithelial cells (MCF10A) silenced for WWOX expression by means of shRNA (short hairpin RNA) showed significant resistance to the DNA damaging effects of bleomycin surviving 25‐fold better at 1 and 1.5 μg/mL and 100‐fold better at 3 μg/mL when compared with WWOX expressing controls (shScr). Increased survival of MCF10A WWOX silenced cells was also observed when exposed to IR at 7.7 Gy and above compared to WWOX sufficient cells (Figure B) . We observed similar results in Wwox KO mouse embryonic fibroblasts (MEFs) when compared with wild‐type (WT) counterparts, with Wwox KO cells surviving 10‐fold better than WT cells when exposed to IR doses of 7.7 Gy and above, and such IR resistant phenotype in Wwox KO MEFs was reverted upon ectopic Wwox expression .…”
Section: Wwox As a Contributor To Genomic Instabilitysupporting
confidence: 66%
See 2 more Smart Citations
“…As illustrated in Figure A, normal breast epithelial cells (MCF10A) silenced for WWOX expression by means of shRNA (short hairpin RNA) showed significant resistance to the DNA damaging effects of bleomycin surviving 25‐fold better at 1 and 1.5 μg/mL and 100‐fold better at 3 μg/mL when compared with WWOX expressing controls (shScr). Increased survival of MCF10A WWOX silenced cells was also observed when exposed to IR at 7.7 Gy and above compared to WWOX sufficient cells (Figure B) . We observed similar results in Wwox KO mouse embryonic fibroblasts (MEFs) when compared with wild‐type (WT) counterparts, with Wwox KO cells surviving 10‐fold better than WT cells when exposed to IR doses of 7.7 Gy and above, and such IR resistant phenotype in Wwox KO MEFs was reverted upon ectopic Wwox expression .…”
Section: Wwox As a Contributor To Genomic Instabilitysupporting
confidence: 66%
“…Failure of proper DNA damage response is, therefore, the most common cause of genomic instability in eukaryotic cells . Recently we provided evidence that WWOX is not only a common target affected by genomic instability, as summarized in previous sections, but it also exhibits a genome caretaker function influencing DNA DSBs repair pathway choice . Interestingly, we observed that human and mouse cells deficient in WWOX expression displayed survival advantage following treatment with agents that induce DNA DSBs, such as radiomimetic bleomycin and ionizing radiation (IR).…”
Section: Wwox As a Contributor To Genomic Instabilitymentioning
confidence: 83%
See 1 more Smart Citation
“…It was also suggested that WWOX might serve as a genome caretaker, with its function based on Brca1-Wwox interaction in turn supporting NHEJ as the principal DSB repair pathway in Wwox-expressing cells (64). …”
Section: Wwox In Dna Damage Response and Genomic Stabilitymentioning
confidence: 99%
“…It seems more logical that evolution would select against an unstable locus encoding a genome caretaker function, yet the evidence in mice and human cells indicate it has been conserved in mammals. Moreover, another putative DNA caretaker, WWOX, is encoded at the other most fragile CFS, FRA16D . Thus, for unknown reasons, evolution may have allowed on more than one occasion an unstable locus to encode a genome‐stabilizing function.…”
Section: Genomic and Chromosomal Alterations Triggered By Fhit Lossmentioning
confidence: 99%